Effect of moringa extract on parasitemia, monocyte activation and organomegaly among Mus musculus infected by Plasmodium berghei ANKA - Budiapsari, Putu I.; Jaya, Putu KD.; Dewi, Pande MACPN.; Laksemi, Dewa AAS.; Horng, Jim-Tong (Narra J, 2024)
In Indonesia, malaria remains a problem, with 94,610 active cases in 2021 and its current therapy includes chloroquine and artemisinin; however, resistance has been commonly reported. To overcome this problem, studies about potential medicinal plants that can be used as antimalaria, such as moringa (Moringa oleifera) started to receive more attention. The aim of this study was to investigate the effects of moringa in parasitemia, monocyte activation, and organomegaly on animal model malaria. This experimental study used male Mus musculus, infected by Plasmodium berghei ANKA, as an animal malaria model. The extract was made by maceration of dry moringa leaves, which were then divided into three concentrations: 25%, 50%, and 75%. Dihydroartemisinin-piperazine was used as a positive control treatment, and distilled water as a negative control treatment. The animals were observed for six days to assess the parasitemia count and the number of monocyte activation. On day 7, the animals were terminated, and the liver, spleen, and kidney were weighed. The results showed that the effective concentrations in reducing parasitemia and inducing monocyte activation were 50% and 25% of moringa leaf extract, respectively. The smallest liver and spleen enlargement was observed among animals within the group treated with a 50% concentration of M. oleifera extract. In contrast, the smallest kidney enlargement was observed in the group treated with 25% of M. oleifera extract. Further analysis is recommended to isolate compounds with antimalarial properties in moringa leaves.